(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article explores the international trends in the development of digital platforms in e-commerce. With the rapid evolution of technology and changing consumer preferences, businesses are constantly adapting their strategies to stay competitive in the digital marketplace. Key trends such as mobile commerce, omnichannel marketing, personalization, AI, and blockchain technology are shaping the future of e-commerce platforms, driving innovation and enhancing the overall shopping experience for customers.